Alcohol use and depression - literature review - Płaczek, Alicja; Białas, Filip; Baciur, Patrycja; Skowrońska, Katarzyna; Chmura, Anna (Journal of Education, Health and Sport, 2022)
Alcohol consumption has serious health and social consequences. A coexistence of alcohol use disorders and depressive disorders is common. Alcohol abuse is more common in men, but women are at greater risk of its harmful effects. Alcohol consumption in adolescence and early adulthood is associated with a higher risk of developing depressive disorders in the future. The order in which these disorders appear may vary, but it is important to make a diagnosis of depression during the period of abstinence. Drinking alcohol can be seen as a form of coping with stress and anxiety disorders. The aim of this article is to review the literature on the relationship between depression and alcohol. Alcohol changes your neural pathways. Long and intense exposure may cause irreversible changes. The stress response pathways responsible for emotions and the reward system are the most sensitive. They deregulate the hypothalamic-pituitary-adrenal axis. Coexistence of alcohol use disorders and depressive disorders is treated primarily with antidepressants. Cognitive behavioral therapy has been shown to have a modest positive effect in relieving symptoms of depression and reducing the amount of alcohol consumed.